APPLICATION OF AN ANTISEPTIC PREPARATION "POVIDON-IOD" IN COMPLEX TREATMENT OF SOFT TISSUES PYOINFLAMMATORY PROCESSES - Nemchenko, I.I.; Lachovskiy, V.I.; Dudchenko, M.A.; Kovalyov, A.P.; Lulka, A.N.; Кравців, М.І.; Dmitrenko, V.; Nemchenko, L.B. (World of Medicine and Biology, 2012)
Examination of the 36 patients with soft-tissues pyoinflammatory processes, who were under treatment in Surgical Department №1 of the 2nd CCH in Poltava took place. In the complex treatment of those patients antiseptic medicine “Povidon - Iod” been used topically. Rates of the traumatic process clinical course and wounds microbiological sowing were investigated. According to the results of the clinical-laboratory researches was determined, that topical usage of the “Povidon - Iod” in complex treatment of soft-tissue pyoinflammatory processes gives an opportunity to reduce the term of the antibacterial therapy and accelerate wounds healing, which has a positive impact as on clinical as on pharmacologic-economical effect of treatment.